Analisis Al-Muwazanah pada Qur’an Surah Al-Ghasiyah - Nur Zakiah Harahap; Siti Rahmah; Harun Ar-Rasyid (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Muwazanah is one of the balaghah discussions in the study of badi' science. Muwazanah is included in muhasinat al-lafdziyyah, namely studies in Ilmubadi' which discusses the beauty of language related to lafadz. Language style itself is a way to express or express feelings both in writing and verbally. Muwazanah in balaghah science is an analytical method used to compare two or more texts or expressions in terms of language beauty, structure and meaning. This approach aims to assess the effectiveness of rhetoric and writing style, as well as to explore the depth of meaning contained in literary works. By conducting muwazanah, researchers can identify the strengths and weaknesses of each text, thereby providing deeper insight into communication techniques and aesthetic appeal. The results of this muwazanah can enrich understanding of balaghah and its contribution to the art of speaking and writing in a cultural and literary context.